TI_GERICHTE 15.2015.29 vom 5. Juni 2015 , Ricorso contro il verbale di pignoramento. Termine di partecipazione al pignoramento - TI Tribunale d'appello (2015)
Ricorso contro il verbale di pignoramento. Termine di partecipazione al pignoramento